The Effect of Risk Factors on Cardiovascular Diseases in Thi-Qar Governorate: Pengaruh Faktor Risiko terhadap Penyakit Kardiovaskular di Kegubernuran Thi-Qar - Kazim , Hajar Abdelkarim; Salman , Ali Naeem (Indonesian Journal on Health Science and Medicine, 2025)
The purpose of this research was to identify the role of risk variables in the onset and progression of cardiovascular illnesses. There was a significant difference (P ≤0.05) between the two groups, with the sick group having a 36% higher smoking rate than the control group's 12% rate. A comparison between the patient group and the control group revealed that total cholesterol, triglycerides, and low-density lipoprotein (LDL) concentrations were all higher in the former, while HDL concentrations were lower. With 64% of patients experiencing hypertension and 36% not experiencing it, the percentages of patients with hypertension and those without it are much greater. There was a greater prevalence of type 2 diabetes among patients (60% vs. 40%), as well as other metabolic disorders. Among the other findings, 38% of patients were considered to be at a normal weight, 40% were considered to be overweight, and 24% were classified as having first-class obesity Highlights: Higher smoking rate, cholesterol, LDL, and lower HDL in patients. Increased hypertension (64%) and type 2 diabetes (60%) prevalence. 40% overweight, 24% obese, 38% normal weight among patients. Keywords: Heart and Vascular diseases, Rask Factors.